Sexual Harassment: Prevalence, Predictors, and Associated Outcomes in Late Adolescence. - Wood, Leila; Baumler, Elizabeth; Mytelka, Caitlyn; Knutson, Chelsea; Temple, Jeff R. (Child & Adolescent Social Work Journal, 2026)
Despite the potential for negative health consequences, scant recent literature has focused on sexual harassment among older adolescent populations. In assessing the prevalence, predictors, and outcomes of this persistent public health problem, we begin to address this gap in knowledge. As part of an ongoing longitudinal study, we administered the Sexual Experiences Questionnaire to 1,124 older adolescents (17 and 18) and conducted multilevel logistic regression analyses to examine the link between demographic, environmental, and health factors and sexual harassment. 20% of older adolescents reported being sexually harassed in the past year. Girls were twice as likely and bisexual/pansexual participants were three times as likely to experience harassment, relative to males and heterosexual participants, respectively. Sexual harassment was associated with multiple health problems (PTSD, anxiety, and depression) and frequency of alcohol use. It was inversely related to positive school peer climate. Findings underscore the health consequences of sexual harassment, especially for female and gender and sexual minority adolescents, who are at higher risk. Interventions focused on improving mental wellbeing should include sexual harassment prevention and vice versa. Given our finding that positive school climate is associated with less sexual harassment, school-based interventions should be employed to promote a harassment-free environment.